Design of Power Amplifier for UWB Radar - J. Dighe, Viresh; Srivastava, Poornima; Nair, Sreedevi (International Journal of Engineering and Technology, 2018)
This paper discusses the design of the power amplifier for UWB Radar. The power amplifier design is one of the important aspect of the UWB Radar as it helps in increasing the transmission range. The impedance matching is done by stub matching. The design of the power amplifier is done by using ADS software. The design frequency for the power amplifier is 6 GHz. The reason for choosing 6 GHz as design frequency is less rain fade in the communication channel, the larger bandwidth available at cheaper price. The bandwidth of 1.5 GHz is chosen so as to satisfy the FCC requirement of bandwidth to be greater than or equal to 0.25 times of center frequency. The UWB technology is used in various applications such as through-wall detection, airport-surveillance, obstacle detection.Â Â